Local tourists assessment on the popularity of the selected restaurants offering kapampangan dishes in San Fernando, Pampanga - Angeles, Juliet Angeline R. Balitaan, Sharlyn D. Barrera, Edison A. Bautista, Annalie B. 4 0 16; 5 (2015)
The aim of this study is to assess the popularity of the selected restaurants offering Kapampangan dishes in San Fernando, Pampanga with the local tourists as respondents to know the potential of these restaurants for culinary tourism. descriptive correlational research design and convenience sampling method were used in this study. the researcher made questionnaire served as the main data gathering instrument with an interview guide as support. the researchers asked for permission from the concerned tourist offices and restaurants to conduct survey and interview that were validated by experts. the distribution of questionnaires and interviewing were accomplished during the three day stay in San Fernando, Pampanga. Results were described using frequency-distribution table and the weighted mean and analyzed through the Pearson Product Moment Correlation Coefficient (Person r), One-way analysis of Variance (ANOVA) and the T-test difference Results showed that all of the selected restaurants in terms of its menu, service, and atmosphere / ambiance were good as perceived by the local tourists. In summary, the researchers recommended to increase promotions of these selected restaurants offering kapampangan dishes through information dissemination, brochures and social media. Also, the restaurants should improve their facilities and services to satisfy the tourists and customers more. The local tourism offices were recommended to have exhibitions and conventions featuring restaurants offering Kapampangan dishes and others to promote the tourism industry of San Fernando, especially its culinary tourism.
Undergraduate Thesis (BS in Travel and Tourism Management) Pamantasan ng Lungsod ng Maynila 2015.
Keywords: 2 -- 0; 6; 20; 20; 2